2016
DOI: 10.1007/7854_2016_41
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationships of Synthetic Cathinones

Abstract: Until recently, there was rather little interest in the structure-activity relationships (SARs) of cathinone analogs because so few agents were available, and because they represented a relatively minor drug abuse problem. Most of the early SAR was formulated on the basis of behavioral (e.g. locomotor and drug discrimination) studies using rodents. With the emergence on the clandestine market in the last few years of a large number of new cathinone analogs, termed “synthetic cathinones”, and the realization th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 51 publications
(79 reference statements)
2
69
0
Order By: Relevance
“…Pentylone, conversely, has been described as an uptake inhibitor 5 to 8-fold selective for DAT over SERT (Costa et al 2018;Eshleman et al 2018), a nonselective uptake inhibitor (Eshleman et al, 2017), a "hybrid" compound (Simmler et al, 2014;Saha et al, 2018), or a weak DAT/ SERT substrate (Dolan et al, 2018). Previous analyses of structure-activity relations among synthetic cathinones have demonstrated that tertiary amine substitution (as in dimethylone and dibutylone) or substitution with larger alkyl groups (as in ethylone or N-ethylpentylone) confers transporter-blocking properties to compounds (Kolanos et al, 2013;Solis, 2017;Glennon and Dukat, 2017), so the unstudied compounds currently under investigation potentially have more-prominent transporter-blockade effects relative to their mono-and methyl-substituted counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Pentylone, conversely, has been described as an uptake inhibitor 5 to 8-fold selective for DAT over SERT (Costa et al 2018;Eshleman et al 2018), a nonselective uptake inhibitor (Eshleman et al, 2017), a "hybrid" compound (Simmler et al, 2014;Saha et al, 2018), or a weak DAT/ SERT substrate (Dolan et al, 2018). Previous analyses of structure-activity relations among synthetic cathinones have demonstrated that tertiary amine substitution (as in dimethylone and dibutylone) or substitution with larger alkyl groups (as in ethylone or N-ethylpentylone) confers transporter-blocking properties to compounds (Kolanos et al, 2013;Solis, 2017;Glennon and Dukat, 2017), so the unstudied compounds currently under investigation potentially have more-prominent transporter-blockade effects relative to their mono-and methyl-substituted counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…By “mixing and matching” the various substituents, certain cathinone analogs could possess “mixed” or “hybrid” actions. 75 This, once again, underscored the concept that small structural alterations to the phenylalkylamine scaffold can have a significant impact on pharmacology.…”
Section: Synthetic Cathinonesmentioning
confidence: 99%
“…Bath salts was initially a combination of methylone (MDMC; 59 ) – the β-keto analog of MDMA ( 43 ), mephedrone ( 60 ), methylenedioxypyrovalerone (MDPV; 61 ; Figure 13), or one or more of these agents in combination with other (known or novel) phenylisopropylamines (reviewed 74,75 ).Today, the term “bath salts” is often used rather generically to refer to almost any synthetic cathinone. Over the past 5 or 6 years, approximately 150 different synthetic cathinones have been confiscated from the clandestine market.…”
Section: Synthetic Cathinonesmentioning
confidence: 99%
See 2 more Smart Citations